2022
DOI: 10.3390/jcm11143958
|View full text |Cite
|
Sign up to set email alerts
|

Relative Efficacy and Safety of Anti-Inflammatory Biologic Agents for Osteoarthritis: A Conventional and Network Meta-Analysis

Abstract: Previous studies have consistently revealed that both local and systemic inflammations are the key to the onset and progression of osteoarthritis (OA). Thus, anti-inflammatory biologic agents could potentially attenuate the progression of OA. We conducted this meta-analysis to examine the efficacy and safety of ant-inflammatory biologic agents among OA patients. Methods: Five databases were searched for randomized controlled trials (RCTs) comparing biologics with placebo or each other in OA patients. Data of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The investigators noticed that inflammatory factor levels escalated in patients with knee OA [ 12 , 13 , 14 ]. Developing targeting treatment of the factors, such as synthetic IL-1Ra anakinra or anti-inflammation biologics such as TNF inhibitors is straightforward, and the effects of some biologics have been evaluated and proven in patients with OA [ 41 ]. However, the cost of biologics is a barrier to approach.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators noticed that inflammatory factor levels escalated in patients with knee OA [ 12 , 13 , 14 ]. Developing targeting treatment of the factors, such as synthetic IL-1Ra anakinra or anti-inflammation biologics such as TNF inhibitors is straightforward, and the effects of some biologics have been evaluated and proven in patients with OA [ 41 ]. However, the cost of biologics is a barrier to approach.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence on the effectiveness of these drugs for OA pain is limited. A meta-analysis suggested that etanercept and infliximab were superior to placebo for pain in KOA, and infliximab was superior to the other biologic agents (adalimumab, anakinra, canakinumab, etanercept, naproxen, and tocilizumab) in improving pain in the hands and knees of OA [80]. In contrast, several clinical trials have been reported that specifically for OA of the hand, none seem to have shown the efficacy of a monoclonal antibody against TNF-α and IL-6 [81][82][83].…”
Section: Anti-inflammatory Cytokine Drugsmentioning
confidence: 99%
“…However, the data should be confirmed in future studies as the conclusion regarding infliximab was drawn based on the results of two studies that incorporated 26 patients and combined data with different doses, routes of administration, and localizations of OA (hand and knee OA). The authors hypothesized that females and inflammatory phenotypes of OA with the presence of synovitis and effusion could be potential candidates for treatment with infliximab [ 26 ].…”
Section: Future Directions Regarding Therapeutic Strategies For Osteo...mentioning
confidence: 99%